PERANCANGAN BRAND IDENTITY UMKM STEAK IJOW JALANAN DALAM UPAYA MENINGKATKAN BRAND AWARENESS DI MADE BLEZ STUDIO - Mutiara Anjani, Ni Made Ayu Cantika; Bayu Artha, I Gede Agus Indram; Sri Purnami, Putu Wahyuning (Program Studi Desain Komunikasi Visual, 2024)
In this modern era, international food is increasingly popular in Indonesia. Many restaurants or places to eat that sell international food are spread across several cities in Indonesia. One of the places that sells international food is Jalanan Ijow Steak. This business carries the concept of an angkringan or street stall that sells chicken steak as its main menu. This business is considered to be just starting out in 2024. The obstacle faced before forming this business is how to introduce Street Ijow Steak to the wider community. So the effort that needs to be made to be able to carry out marketing is to design a brand identity or what is often known as branding. The method used by the author to solve this problem is to use a qualitative descriptive method. The initial stage of this design is conducting observations and interviews with clients first. Then the author conducted research independently. After that, the author did brainstorming and mind mapping first to determine the logo concept. Then the author immediately executed these ideas and concepts to create 4 alternative logo designs. After selecting an alternative logo design, then proceed to the stage of creating a digital logo using the Adobe Illustrator application. This brand identity design resulted in Brand Guidelines for Steak Ijow Jalanan. The results of designing the Steak Ijow Jalanan brand identity were then applied to several print media such as banners, x banners, packaging, menus and merchandise.